Note: You probabily forgot to mention the two function. While after some research, I was able to find two functions based on which I would like to solve your query.
Answer:
The y-intercept of the equation will be (0, 4).
Step-by-step explanation:
Considering the assuming functions f(x) and g(x).
![f(x) = -3x - 5](https://tex.z-dn.net/?f=f%28x%29%20%3D%20-3x%20-%205)
![g(x) = f(x)+9](https://tex.z-dn.net/?f=g%28x%29%20%3D%20f%28x%29%2B9)
So,
∵ ![g(x) = f(x)+9](https://tex.z-dn.net/?f=g%28x%29%20%3D%20f%28x%29%2B9)
Now, finding the y-intercept
so putting x = 0 in function g(x)
![g(x) = -3(0)+4](https://tex.z-dn.net/?f=g%28x%29%20%3D%20-3%280%29%2B4)
![g(x) = 0+4](https://tex.z-dn.net/?f=g%28x%29%20%3D%200%2B4)
![g(x) = 4](https://tex.z-dn.net/?f=g%28x%29%20%3D%204)
Therefore, the y-intercept of the equation will be (0, 4).